Amino acid, antioxidant and ion profiles of carpolobia lutea leaf (Polygalaceae) - Nwidu, Lucky Legbosi; Cilli, Eduardo Maffud [UNESP]; Vilegas, Wagner [UNESP] (My University, 2012)
Purpose: To evaluate the amino acid, antioxidant and ionic profiles of Carpolobia lutea leaf (Polygalaceae) extract (CLL). Methods: The powdered leaf was macerated and subjected to gradient solvent extraction with nhexane, chloroform, ethyl acetate and ethanol for 72 h to obtain their respective fractions. Amino acid analysis was by cation-exchange chromatography using automated amino acid analyser. Antioxidant potential was obtained by spectrophotometric assay using 2, 2-Diphenyl-1-picrylhydrazyl DPPH while elemental and ionic analyses were carried out by atomic absorption spectrophotometry and potentiometric titration, respectively. Results: Proline, alanine, serine, valine, glycine, glutamate and lysine were found in the ethanol fraction while lysine, phenyl alanine, glycine and serine were present in the ethyl acetate fraction but not in the non-polar fractions, n-hexane and chloroform. The ethyl acetate fraction contained more lysine, phenyl alanine, glycine and serine the other leaf fractions. Minimal radical scavenging activity of all the fractions was recorded. The most abundant cations in the extract were potassium and phosphorus (2.16 ± 0.05 and 1.90 ± 0.06 mg/g, respectively) while the most abundant anion was phosphate with a concentration of 23.23 ± 4.61 mg/g for the aqueous leaf fraction Conclusion: The study shows that CLL fractions contain variety of amino acids which could promote wound healing, as well as major and minor elemental ions which, as essential body electrolytes, are required for various metabolic processes in the body. © Pharmacotherapy Group.
Keywords: Amino acid; Antioxidant; Carpolobia leaf; Ionic profile; Polygalaceae